Factors Affecting on the Voluntary of Personal Tax Income Payment in Eastern Region - Pimsuwan, Wiriyasita; Saengkhiew, Porntiwa (Rajapark Journal, 2021)
The objective of this study was to study the factors of personal income tax. Consisting of knowledge and understanding of taxation receiving information and news service satisfaction, attitude, tax rate paid affecting the voluntary income tax payment in the field of on-time filing of individual taxpayers in the eastern region and the accuracy of individual income earners in the eastern region. This study was a quantitative research. The sample group used in the study was the population in the eastern region as follows: Chonburi, Rayong, Chachoengsao, Trat, Chanthaburi, Prachinburi, and Sakaeo. The researcher was distributed the questionnaire directly to the sample of 400 samples using the quota sampling method. Data were collected via questionnaire perform analysis using basic statistics. The results of the study showed that factors affecting the voluntary income tax payment in terms of on-time filing and the accuracy of individual taxpayers in the eastern region. The attitude factor affected the voluntary income tax payment in term of on-time filing in positive was statistically significant at 0.01 level. Moreover, the information obtaining, and the attitude factor affected the voluntary personal income tax payment in term of accuracy in positive was statistically significant at 0.01 level.